Post-fire effects of invasive exotic plants on seed banks, regeneration, soil chemistry and selected soil microbial populations in the Silvermine Nature Reserve, Cape Peninsula, South Africa - Cilliers, Charl Daniel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2002.